دور السّلطة الوطنيّة المستقلّة في ظلّ الأمر21-01 المتضمّن القانون العضوي للانتخابات - (:unkn) unknown (جامعة الوادي university el-oued, 2022)
بعد تعديل دستور سنة 2020، وذلك باستحداث السلطة الوطنية المستقلة للانتخابات في ظل الأمر 21-01 ، المتضمن القانون العضوي للانتخابات، مفصلا في طبيعتها القانونية وتنظيمها وإشرافها وتسييرها وصلاحياتها في العمليات الانتخابية بكل مراحلها من استدعاء الهيئة الناخبة إلى الإعلان المؤقت وكذلك اسند لها عملية الرقابة التي تكون اما تدخل تلقائيا في حالة وجود اختلالات واعتداءات مخالفة للقوانين المعمول به، اضافة الى تدخل السلطة الوطنية المستقلة في حالة المنازعات الانتخابية اما اعتبارها جهة مختصة للفصل في الطعون والتظلمات الادارية من ذوي الصفة والمصلحة او باعتبارها طرف في المنازعات وذلك من خلال الطعن في قراراتها ، قضائيا او دستوريا.After amending the Constitution of 2020, and by creating the Independent National Authority for Elections in the light of order 21-01, that includes the Organic Law of Elections, give a lot of details of its legal nature, organization, supervision, management and powers in the electoral processes in all its stages, from summoning the electorate to the temporary announcement; therefore, entrusting it with the oversight process that It either enters automatically in the event of irregularities and attacks in violation of the laws in force in addition to the intervention of the independent national authority in the event of electoral disputes, or constitutional.
مذكرة ماستر
Keywords: : تعديل الدستور، إصدار الأمر، السلطة الوطنية المستقلة للانتخابات،العمليات الانتخابية.; amending the constitution, order issue, Independent National Electoral Authority, electoral processes .